Funkcje nazw własnych w dyskursie tożsamościowym. Na podstawie wybranych powieści i opowiadań historycznych Elżbiety Cherezińskiej i Jacka Komudy = Functions of proper names in the identity discourse. Based on selected historical novels and stories by Elżbieta Cherezińska and Jacek Komuda - Szagun, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Names as an element of cultural memory build our identity through a simple recall of history, but above all by a special exhibition of old events. In this way, the presence of proper names, in the genre characteristic for establishing the sense of national identity, which is a historical novel, also recreate the identity discourse by recalling and repeating history.
Keywords: dyskurs; tożsamość; powieść historyczna; nazwa własna; discourse; identity; historical novel; proper name